The Texas shoot-out under Knightian Uncertainty - Gerrit Bauch; Frank Riedel (Bielefeld University, Center for Mathematical Economics (IMW), 2022)
The allocation of a co-owned company to a single owner using the Texas Shoot-Out mechanism with private valuations is investigated. We identify Knightian Uncertainty about the peer's distribution as the reason for its deterrent effect of an immature dissolving. Modeling uncertainty by a compact environment around a reference distribution F in the Prohorov metric, we derive the optimal price announcement for an ambiguity averse divider. The divider hedges against uncertainty for valuations close to the median of F, while extracting expected surplus for high and low valuations. The outcome of the mechanism is efficient for valuations around the median. A risk neutral co-owner prefers to be the chooser, even strictly so for any valuation under low levels of uncertainty and for extreme valuations under high levels of uncertainty.
urn:nbn:de:0070-pub-29624095
Keywords: C72; D74; D81; D82; 330; Knightian Uncertainty in Games; Texas Shout-Out; Partnership Dissolution